Mode of loading on flexural fatigue laboratory properties of conventional and asphalt-rubber mixes : a model validation - Sousa, Jorge B. (2003)
Traditionally the correct modeling and prediction of asphalt fatigue mechanisms, has re-lied on the use of the appropriate mode of loading in laboratory tests. The mode of load-ing chosen should, as closely as possible, reflect the mode of loading that causes crack propagation in the field. However recent formulations may be opening the door to the determination of key parameters from either mode of loading. Fatigue characterization using any model must recognize that controlled load or dis-placement will induce significantly different fatigue lives in laboratory tests. When those lives must be correlated to actual field performance the magnitude and the accuracy of the shift factor is strongly affected by the mode of load selected in the laboratory material characterization phase. Asphalt-Rubber Hot-Mix (ARHM) has shown a higher resistance to flexural than con-ventional Dense Graded Asphalt Concrete (DGAC). This paper presents the results of four point flexural fatigues tests performed under load and under displacement control on conventional and asphalt rubber mixes and investigates the applicability of an intrinsic damage law in light of the observed experience.